2012
DOI: 10.1016/j.bcp.2011.12.039
|View full text |Cite
|
Sign up to set email alerts
|

Stereoisomers ginsenosides-20(S)-Rg3 and -20(R)-Rg3 differentially induce angiogenesis through peroxisome proliferator-activated receptor-gamma

Abstract: Ginsenosides are considered the major constituents that are responsible for most of the pharmacological actions of ginseng. However, some ginsenosides exist as stereoisomeric pairs, detailed and molecular exposition based on the structural differences of ginsenoside stereoisomers has not been emphasized in most studies. Here we explore the functional differences of ginsenoside Rg₃ stereoisomers on angiogenesis. In this study, we demonstrated the distinctive differential angiogenic activities of 20(S)-Rg₃ and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
43
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 47 publications
1
43
0
Order By: Relevance
“…Among them, Diospyros bipindensis was identified as the most interesting plant for possible activity on PPARs receptors. In fact, some plants of the same family and genus are known to have anti-inflammatory, anti-diabetic and hypoglycaemic properties 2430 . Diospyros bipindensis has been studied, and some secondary metabolites have been purified and identified including plumbagin, betulinic acid, caniculatin, 4-hydroxy-5-methyl-coumarin and ismailin 22 (Figure S1 of Supplementary Information).…”
Section: Introductionmentioning
confidence: 99%
“…Among them, Diospyros bipindensis was identified as the most interesting plant for possible activity on PPARs receptors. In fact, some plants of the same family and genus are known to have anti-inflammatory, anti-diabetic and hypoglycaemic properties 2430 . Diospyros bipindensis has been studied, and some secondary metabolites have been purified and identified including plumbagin, betulinic acid, caniculatin, 4-hydroxy-5-methyl-coumarin and ismailin 22 (Figure S1 of Supplementary Information).…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis assay found that both Rg3 stereoisomers can induce differential angiogenesis effects via PPARγ, and the PPARγ agonist activity of 20(S)‐Rg3 is 10 times stronger than that of 20(R)‐Rg3 11. A fluorescence polarization and total internal reflection fluorescence (FP‐TIRF) binding study also confirmed that only 20(S)‐Rg3 can quantitatively bind to the PPARγ ligand‐binding domain (PPARγ‐LBD) 12.…”
Section: Introductionmentioning
confidence: 80%
“…The importance of drug stereoselectivity is gaining greater attention in recent years,32 and differential pharmacological effects have been reported between ginsenoside Rg3 stereoisomers 9, 11, 12. It is because although the enantiomers of Rg3 possess the same functional group at C20, the difference in three‐dimensional structure may affect the binding affinity to the receptor binding site.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The peroxisome proliferator activated receptor-γ activity of 20(S)-Rg3 is 10-fold higher than that of 20(R)-Rg3 [18]. 20(R)-Rg3 has more potent activity than 20(S)-Rg3 in stimulating the immune response [19].…”
Section: Introductionmentioning
confidence: 96%